Struktur Kepemilikan dan Manajemen Laba : Tinjauan Literatur Sistematis Berdasarkan Teori Keagenan - Muh Taufiq; Sakia Putri Samsul; Muh. Risnandar; Linda Arisanti Razak; Amril Amril (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to examine the relationship between ownership structure and earnings management practices using a Systematic Literature Review (SLR) approach based on the agency theory perspective. Ownership structure—encompassing institutional, managerial, and concentrated ownership—is viewed as an internal control mechanism with the potential to mitigate agency conflicts and opportunistic management behavior. The literature search was conducted systematically through national and international academic databases, covering publications from 2021 to 2025, resulting in 25 scientific articles that met the inclusion criteria for analysis. The synthesized results indicate that institutional ownership tends to play a role in suppressing earnings management practices through more effective monitoring functions, though its influence largely depends on the ownership proportion and institutional context. Meanwhile, managerial ownership exhibits a dual effect: it can align the interests of managers and shareholders at certain levels, yet potentially increases earnings management when ownership is high or under external pressure. Furthermore, the effectiveness of ownership structures is influenced by complementary corporate governance mechanisms, such as audit quality and corporate social responsibility disclosure. This research is expected to provide theoretical and practical contributions to improving the quality of financial reporting.